1971
DOI: 10.1152/ajplegacy.1971.220.6.1779
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic mechanisms in canine mesenteric circulation

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

1973
1973
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 0 publications
1
15
1
Order By: Relevance
“…Increased sympathetic activity constricts the mesenteric arterioles and capacitance vessels. These responses are mediated by α-adrenergic receptors, which are predominant in the mesenteric circulation; however, β-adrenergic receptors are also present [52].…”
Section: Influence Of Neural Factorsmentioning
confidence: 99%
“…Increased sympathetic activity constricts the mesenteric arterioles and capacitance vessels. These responses are mediated by α-adrenergic receptors, which are predominant in the mesenteric circulation; however, β-adrenergic receptors are also present [52].…”
Section: Influence Of Neural Factorsmentioning
confidence: 99%
“…But it is speculated that its inhibitory effects do not depend on the activity o f exogeneous gut hormones and pancreatic blood flow [1,4,7,8], but that it acts on the nerve o f the acinar cells o f the pancreas [1,4]. In other words, these observations support evidence that (3-adrenergic stimulators act in the splanchnic nervous system o f the acinar cells, resulting in inhibition o f the exocrine pancreatic secretion.…”
Section: Discussionmentioning
confidence: 95%
“…The increase of INA during norepinephrine administration is in a direction opposite to the expected effect of the four major baroceptor reflex. It has been shown that the injection of epinephrine or norepinephrine causes the portal blood pressure to increase (SEMBA, 1954;SWAN and REYNOLDS, 1971). Although the origin of the increase in INA during norepinephrine administration is not yet clear, recent findings (ANDREWS et al, 1972) of the presence of mesentery "venous volume" or "stretch" receptors in the portal vein suggest that norepinephrine caused the portal blood pressure to increase and this in turn caused an increase in the efferent nerve discharge to the intestine.…”
Section: Resultsmentioning
confidence: 99%